Legal Impact Theory in the Context of an Integrative Approach to Understanding Law - Palekha, Roman R.; Belyaev, Valery P.; Kanishchev, Valery P.; Solovyova, Larisa L.; Turanina, Neonila A. (Cuestiones Políticas, 2020)
The theory of legal impact from the perspective of an integrative approach to understanding law, is a progressive theoretical and methodological toolkit with a high potential of heuristically mastering of various legal phenomena. This theory understood within the framework of an integrative approach, allows us to consider its legal nature, content and essence as fully and thoroughly as possible, which creates favorable conditions for achieving the criteria of scientific research, such as: comprehensiveness, objectivity, and historicism. It is the integrative approach that makes it possible to fully realize such a fundamental principle of scientific research as unity in diversity, to study the nature of the legal impact comprehensively and deeply, as a complex socio-legal phenomenon, determined by various factors of public life. The methodological ground of the examination depends on the utilization of different general logical procedures and techniques for logical information, just as specific logical strategies – recorded legitimate, formal-lawful, relative lawful and interpretative. Results showed that law isn’t reducible to the arrangement of lawful standards, it is a lot more extensive and progressively various, which is related with its source, bearer and vehicle - a man, with his intentionally solid willed nature and passionate mental motivations.